EMOTIONAL INTELLIGENCE MODEL TO IMPROVE RESILIENCE IN UNIVERSITY STUDENTS - Pumaleque, Alex Abelardo Pacheco; Arbulu, Ana Cecilia Alvarez; Calle, Cesar Augusto Peñaranda; Gutierrez, Flor Haydee Pineda (The journal of contemporary issues in business and government, 2021)
Emotional intelligence is essential when socializing and adapting to the environment, it allows us to understand how we can influence in an adaptive and intelligent way the emotions of people and of ourselves. In the Peruvian university environment, it is important that students have skills to manage their emotions and face adverse situations. Therefore, an emotional intelligence model is proposed to improve resilience in university students. The research is of an experimental, quantitative and quasi- experimental design, the technique used was the survey and as an instrument the questionnaire that was applied to 58 students about the variables emotional intelligence and resilience. The results show that 27.59% indicate that their level of interpersonal intelligence is regular, 39.66% indicate that their level of intrapersonal intelligence is regular and 32.76% indicate that their level of adaptability is bad. Therefore, adequate emotional intelligence and resilience in students will allow them to handle skills such as interpersonal and intrapersonal intelligence, adaptability, perseverance and self- confidence when facing situations of change in their environment.